Relationship between hemoglobin and red blood cell distribution width ratio and albuminuria in the United States adults aged 20 years and above: a cross-sectional analysis - Li, Guangxin; Li, Guangchao; Xu, Wenyu; Yang, Yanping; Zhang, Jin-an; Zhang, Jing (Frontiers in Nutrition, 2025)
ObjectiveHemoglobin to red blood cell distribution width ratio (HRR) is a novel prognostic indicator of disease, and is also associated with a variety of chronic systemic diseases. However, there are fewer studies on the relationship between HRR and albuminuria. This study aimed to investigate the association between the two subjects.MethodsA total of 13,971 participants aged 20 and older in the National Health and Nutrition Examination Survey (NHANES) between 2007 and 2018. The HRR is the ratio of hemoglobin to the width of the red blood cell distribution. Smoothed curve fitting and multivariate segmented linear regression models were used to study the relationship between HRR and albuminuria. Finally, subgroup analysis and interaction tests were performed to test the stability of the results.ResultsThe results of the univariate analysis showed that HRR was negatively associated with albuminuria (OR = 0.86, p < 0.0001). After further adjustment of potential confounding factors, the smooth curve fitting showed that HRR was nonlinearly related to albuminuria. The inflection point of HRR in multiple segmented linear regression analysis was 1.213. Specifically, when HRR <1.213, (OR = 0.93, 95% CI 0.90, 0.97; p = 0.0007); when HRR ≥ 1.213, (OR = 1.24, 95% CI 1.08, 1.43; p < 0.0001). Subgroup analyses revealed that this association exists as stable in different populations.ConclusionThere was a nonlinear correlation between HRR and albuminuria in adults aged 20 or older in the United States.